2012
DOI: 10.1590/s0103-636x2012000400005
|View full text |Cite
|
Sign up to set email alerts
|

Why is mathematics valuable?: a comparison of Turkish and German mathematics teachers

Abstract: This study was based on the data obtained from "Values in Mathematics Teaching in Turkey and Germany [VMTG]" project which lasted two years. The VMTG project compares German and Turkish mathematics teachers' and their students' values. The purpose of the study is to investigate Turkish and German mathematics teachers' views on why math is valuable, and explore the mathematical values behind their views. The study was undertaken with 9 Turkish and 13 German mathematics teachers. Even though several data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Equally significantly, both these values (i.e. relevance and rationalism) were also found to be embraced by both Turkish and German teachers (Dede 2012). Indeed, Australian primary school teachers were also observed to subscribe to similar values (Bishop et al 2001).…”
Section: Similaritiesmentioning
confidence: 96%
“…Equally significantly, both these values (i.e. relevance and rationalism) were also found to be embraced by both Turkish and German teachers (Dede 2012). Indeed, Australian primary school teachers were also observed to subscribe to similar values (Bishop et al 2001).…”
Section: Similaritiesmentioning
confidence: 96%
“…Equally significantly, both these values (i.e. relevance and rationalism) were also found to be embraced by both Turkish and German teachers (Dede 2012). Indeed, Australian primary school teachers were also observed to subscribe to similar values ).…”
Section: Similaritiesmentioning
confidence: 84%
“…The value indicators and their corresponding values were also categorized into two types of thinking: isolated thinking and connected thinking. Isolated thinking reflects that mathematics is seen as a set of isolated concepts and procedures whereas connected thinking reflects that connected values such as connections among mathematical ideas and ideas from other disciplines usefulness, process, communication, and creativity (see Dede 2012;Ernest 2004). Description of value indicators, their corresponding values, and the types of thinking are summarized in Table 10.1.…”
Section: Resultsmentioning
confidence: 99%
“…Semantic content analysis is the process of creating subcategories to detect themes in a text or phenomenon (Tavşancıl & Aslan, 2001). In this sense, the EBA contents reviewed were analysed based on the values and value signals that emerged in the literature (for example, Bishop, 1988;Dede, 2012Dede, , 2015Dede, , 2019Dede & Barkatsas, 2019;Lim & Ernest, 1997;Seah, 1999Seah, , 2011. As mentioned above, the general educational values have not been analysed in the current study since they do not directly affect students' mathematics achievement (Seah et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although there is less emphasis on progress in distance education courses, it is seen that students place more emphasis on progress in face-to-face classes. In fact, in his research to determine why mathematics is important, Dede (2012) found that Turkish and German mathematics teachers especially gave importance to rationalism and progress values in face-to-face education. Also, Dede (2012) found that rationalism, control, and openness values among mathematics values were emphasised more in textbooks.…”
Section: Mathematical Valuesmentioning
confidence: 99%